2020
DOI: 10.4103/cs.cs_19_41
|View full text |Cite
|
Sign up to set email alerts
|

Sport Hunting to Save Nature? The Case of Uganda

Abstract: After having banned sport hunting in 1979, Uganda reintroduced it in 2001 around Lake Mburo National Park, and in 2006 in the Kabwoya and Kaiso-Tonya Game Management Area, with the aim to reduce human-wildlife conflicts, especially poaching, by providing incentives for the local inhabitants in order to positively change residents' attitudes towards wildlife. We conducted interviews and reviewed documents to analyse and evaluate the impacts of reintroduction of sport hunting. The income generated from sport hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although illegal hunting of all forms was banned in Uganda in 1979 (Amos et al 2020), this was continuing in Madi Corridor as was noted in this study. Generally, all mammal species were targeted by poachers and poaching pressure appeared to have significantly increased with the return of peace in the area and as the community started to return from IDPs to a more settled life.…”
Section: Relationship Between Anthropogenic Activities and Mammal Ass...mentioning
confidence: 63%
“…Although illegal hunting of all forms was banned in Uganda in 1979 (Amos et al 2020), this was continuing in Madi Corridor as was noted in this study. Generally, all mammal species were targeted by poachers and poaching pressure appeared to have significantly increased with the return of peace in the area and as the community started to return from IDPs to a more settled life.…”
Section: Relationship Between Anthropogenic Activities and Mammal Ass...mentioning
confidence: 63%
“…The government's promotion for commercialized and modernized agriculture, further privatization of the land, and sedentarization (Tukahirwa, 2002;Mugisha, 2002;Olson et al, 2004;Byenkya, 2004;Wurzinger et al, 2009) also causes increased settlements and farmlands. Intensified modernized agriculture, for example, rearing of exotic breeds, also requires clearing vegetation to provide grazing land for exotic breeds (Ochieng et al, 2020), causing a reduction in woodland cover outside the park. Katushabe (2014) noted that farmers who adopted exotic species cleared woodland.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that pastoralists are still clearing woodland in their ranches. Built-up areas and farmland increase were further boosted by the government expenditure of proceedings from the sport hunting in supporting arable farming, roads, and semipermanent house construction (Ochieng, 2019;Ochieng et al, 2020). Other factors, such as restricting communal grazing land due to fencing of land by private owners (Kisamba-Mugerwa, 1995) necessitated settlements.…”
Section: Discussionmentioning
confidence: 99%